The modal behavior of violin components - Akar, Özge; Willner, Kai (Proceedings of ISMA 2022 - International Conference on Noise and Vibration Engineering and USD 2022 - International Conference on Uncertainty in Structural Dynamics, 2022)
The violin's versatility in physical effects is given by the numerous interfaces like the bow-string contact or the soundpost clamped between the top and the back plate. Furthermore, there is the geometric nonlinearity of the strings, the anisotropic behavior of the wood material, etc. This is why in present work the bowed-string instrument serves as research subject, aiming at the accurate numerical modeling of the whole violin. Therefore, the authors apply a stepwise approach where they create finite element models based on very accurate 3D scans of violin components. The numerical modal analysis results are compared with the modal parameters that are obtained in experimental modal analyses using 2D scanning laser-doppler-vibrometry. The material parameters applied in the simulation models were obtained via inverse material parameter identifications on the raw woods from which the violin components were made. The main goal is to find out how far model reductions are applicable without losing significant accuracy in the final simulation models.
CRIS-Team Scopus Importer:2024-12-16